The study of cross-reactivity of therapeutic drugs based on monoclonal antibodies on human tissues: basic approaches and methodological techniques - T. Y. Ostroukhova; V. A. Ivanov; E. L. Morozova; R. A. Ivanov (Биопрепараты: Профилактика, диагностика, лечение, 2018)
Tissue cross-reactivity (TCR) studies are screening immunohistochemical (IHC) assays, usually conducted on frozen human and animal tissues. This study is obligatory for getting the permission for clinical trials in Russia for all innovative therapeutic products based on monoclonal antibodies or antibody-like molecules that contain complementarity-determining region (CDR). In this article are represented approaches and methodical features for successful conduction of tissue cross-reactivity studies with examples from own authors’ experience.